ANALISIS PENGARUH TOTAL AKTIVA, PENJUALAN BERSIH DAN LABA SETELAH PAJAK TERHADAP PROFITABILITAS PERUSAHAAN SUBSEKTOR PROPERTY & REAL ESTATE, TBK (STUDI KASUS TAHUN 2016-2018) - jurnalpps pps; Akhmad Rubiyanto; Chamariyah ÔÇÄ; Muninghar ÔÇÄ (Prodi Magister Manajemen Universitas Wijaya Putra, 2020)
This research was conducted in the property & real estate subsector, with a total sample of 48 research companies. The objectives of this study are test and analyze the effect simultaneously of variables: total assets (TA), Net Sales Results (NS) and profit after tax (EAT) on Profitability (ROI) in the Property & Real Estate, Tbk subsector companies in 2016-2018, and then to test and analyze the effect of partial variables of total assets (TA), net sales (NS) and profit after tax (EAT) on profitability (ROI) in the Property & Real Estate, Tbk subsector companies in 2016-2018. This type of research is explanatory research using quantitative approaches.Keywords: total assets (ta), net sales (ns), profit after tax (eat), profitability (roi)